Decomposition of air pollution in Indonesia - Shohibul Manshur Al Ahmad Ana; Suryanto Suryanto; Sarjiyanto Sarjiyanto (BIO Web of Conferences)
The impact of environmental damage and pollution on health and the economy has become a global concern in recent years, including in Indonesia. In Indonesia, the average number of deaths caused by air pollution is 123,000 yearly, and a decrease in life expectancy by 1.4 - 2.4 years by WHO guidelines. This study investigates the decomposition of air pollution (CO2 emissions) in Indonesia from 1995 to 2022. We imposed structural variables comprising urbanization, liberalization, and fossil-based energy. We also associate renewable energy and environmental policy stringency index to describe the decarbonization skeleton. This study uses a dynamic autoregressive distributed approach to examine the interaction between independent variables and carbon emission levels. The results show a diverse influence of urbanization, liberalization, and fossil fuel when associated with skeleton variables that impact the pattern of pollution shaping. Renewable energy is the most critical factor in promoting inclusive decarbonization, while institutional quality is central to generating robust environmental policies. The implication is that a firm commitment is needed to achieve carbon neutrality through clean technology innovation and renewable energy.